The New Education Policy 2020, Digitalization and Quality of Life in India: Some Reflections - Kunnummal Muralidharan; Kulandaivel Shanmugan; Yury Klochkov (MDPI AG, 2022)
The democratic welfare government is not only interested in creating educational institutions as infrastructure for education for all, but is also equally keen on quality-oriented, even-handed, and equitable education. In fact, the focus of the Global Agenda SDG 4 is to raise the standard of living and quality of life by ensuring quality and lifelong education irrespective of region, race, religion, color, and caste, etc. Thus, there is a strong focus in India to reach global targets and more importantly, this is due to the necessity of fulfilling the government's goals on overhauling India's education system in the context of far-reaching changes that have taken place in terms of economic, social, and scientific areas over a period of last twenty years. The outcome of all these complex issues and critical thinking across stakeholders in social development manifested into policy action called the New Education Policy 2020 (NEP 2020). Therefore, it is critically important to analyze the subject under study as a compact system composed of simultaneous relationships to give a combined effect of the objectives and the framework undertaken for the analysis. Quality of life and education are the variables that are difficult to precisely measure in quantitative terms and hence, the implications and inferences are carefully analyzed on the range of issues that are selected for statistical analysis and structural modeling. By going with our estimates, it seems that though NEP 2020 is a popular and mandated educational policy for educational reforms and for a better future, the expected implementation of the policy would be very difficult in the context of digitalization and for raising the quality of life. In our opinion, remarkable progress on the quality of life can be made possible with flexibility in proper life-long education and training, which can culminate skill, experience, quality of education, and rigidity of the segmented labor market into better opportunities and employment.